Local and Metropolitan Communication Systems 1995
DOI: 10.1007/978-0-387-34884-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Cell Rate Monitoring Mechanisms in ATM Systems

Abstract: The control of cell processes plays a central role in ATM network management and strongly influences the overall system overload behavior and the quality of service. One of the crucial control functions is the usage parameter control according to the user-network contract for a connection. Due to the slotted time of the ATM cell process discretetime models are suited for performance analysis. In this paper we first present queueing models operating in discrete-time for the cell rate monitoring, where arbitrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The analysis is based on the algorithm for the computation of the system size distribution in the G[X] / D /1/-S queueing system presented in [15]. This algorithm has been used in [8,12,14] to investigate UPC functions such as the Generic Cell Rate Algorithm (GCRA) and an extension to analyze twodimensional state processes has been presented in [13]. As outlined in the next three subsections, performance measures such as the cell rejection probability, the cell interdeparture time distribution, and the cell delay distribution can be derived easily using the limiting distribution u-(i,j).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis is based on the algorithm for the computation of the system size distribution in the G[X] / D /1/-S queueing system presented in [15]. This algorithm has been used in [8,12,14] to investigate UPC functions such as the Generic Cell Rate Algorithm (GCRA) and an extension to analyze twodimensional state processes has been presented in [13]. As outlined in the next three subsections, performance measures such as the cell rejection probability, the cell interdeparture time distribution, and the cell delay distribution can be derived easily using the limiting distribution u-(i,j).…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning ACR policing can be found in e.g. [19] and [3]. Therefore, the introduction of a SCR as source traffic descriptor is discussed in the standardization bodies.…”
Section: Policing Of Mpeg Video Sourcesmentioning
confidence: 99%
“…The algorithm we present here is of iterative nature and based on the discrete-time analysis of the G I[X] / D /1 -S queueing model presented in [20], which was used in [7] to analyze the GCRA with a renewal process used as input traffic. In [19], an extension of this analysis to deal with ON/OFF input traffic was presented. Based on this, we describe an algorithm to deal with the cyclic occurrence of frames of different types in MPEG coded video sequences due to the coding in GOPs.…”
Section: Cell Loss Analysismentioning
confidence: 99%
“…Research on traffic specifications and policing took off at the advent of ATM networks [10]. In ATM networks, traffic was described in terms of dual Leaky Bucket (LB) parameters: peak and sustainable cell rate and maximum burst size.…”
Section: B Previous Workmentioning
confidence: 99%